Assessment of age at menarche and its relation with body mass index in school girls of Riyadh, Saudi Arabia - Shaik, Shaffi A; Hashim, Rotana T; Alsukait, Sarah F; Abdulkader, Gallia M; AlSudairy, Haifa F; AlShaman, Leena M; Farhoud, Sarah S; Fouda Neel, Mona A (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: Increase of childhood obesity prevalence and rapid changes in socio-economic status resulted in a decline in age at menarche, which contributes, to a number of diseases affecting women’s future health. The objective of this study is to assess the mean age at menarche in girls of ages 9-16 and observe its relationship with their body mass index and other covariates in Riyadh, Saudi Arabia. Materials and Methods: A cross-sectional study was conducted among 304 female students of both private and governmental schools in Riyadh, Saudi Arabia, during March –May 2013. Data on demographics, socioeconomic status, physical activity, diet, and age at menarche were collected from students and their mothers, using self-administered questionnaires. Physical examinations were conducted to collect the anthropometric measurements. Results: Out of 304 students with a mean age (SD) of 12.52(2.08), 165 (54.3%) attained menarche. Mean menarcheal age (SD) for the girls was 12.08 (1.28). The mother’s mean age at menarche was positively correlated with their daughters (r=0.411, P<0.001). There was no significant correlation between BMI and age at menarche (P>0.05). Governmental school students attained menarche at a higher age (12.34) than private school students (11.59), and the difference between them was statistically significant (P<0.001). Conclusion: Schoolgirls in our study attained menarche at an early age with a mean menarcheal age of 12.08 years. Our data follows the globally and regionally observed declining trends of age at menarche. When assessing BMI as an influencing factor of onset of menarche, our results showed no correlation. Further longitudinal studies are encouraged to monitor factors influencing the onset of menstruation, in order to prevent the potentially adverse consequences of early menarche. Asian Journal of Medical Sciences Vol.7(2) 2015 5-12